Intragastric cystogastrostomy in a 4-year-old child with a pancreatic pseudocyst: A novel technique - Akinori Sekioka; Toshiaki Takahashi; Koji Fukumoto; Naoto Urushihara (Wolters Kluwer Medknow Publications, 2018)
Pancreatic pseudocysts (PPs) often occur in association with acute pancreatitis or pancreatic trauma and are uncommon disorders in children. PPs require operative interventions in case they do not disappear spontaneously. There are several interventional treatments, and laparoscopic or endoscopic treatments have been recently reported as a less invasive procedure. However, these procedures are sometimes difficult to perform for small children. We describe a novel intragastric cystogastrostomy with mini-laparotomy for a 4-year-old female child. She presented with a PP caused by trauma. The PP failed to resolve after 6 weeks and we performed open cystogastrostomy. We made mini-laparotomy and inserted a wound retractor into the stomach and expanded both the abdominal and the gastric walls. This procedure created a good operative field and enabled intragastric cystogastrostomy even in small children. There were no complications. At 10-month postsurgery, a follow-up computed tomography showed no recurrence of PP. This novel intragastric cystogastrostomy for PP, which includes the insertion of a wound retractor, is a safe, minimally invasive, and technically feasible approach for younger children with PP. To the best of our knowledge, this is the first report to describe the intragastric cystogastrostomy with a wound retractor.